A Flow-Injection Method for the Determination of the Total Iron using 3,4-Dihydroxybenzaldehyde - Najib, Fadhil M.; Rafiq, Arian (Sulaimani Journal for Pure and Applied Sciences, 1999)
A home-made design flow-injection system has been described in a previous work. This system has been applied in the present work fo r the determination of total iron using the reagent 3,4-dihydroxybenzaldehyde (3,4-DHBA). Optimization of all conditions were as follows: λmax 440 nm., pH of the carrier stream(C.S) 8.8 and its flow rate with the reagent 1.1 ml.min-1, reagent concentration 0.001M and the Manifold length was 60cm. Optimum, linear range of the calibration curve plotted by the method of Least Square with any one of the two equations Y=a+bX or Y=bX; including zero (the blank reading) as one of the standards, was between 0 - 8ppm. total Iron. The accuracy of the method was measured by calculating percentage recovery of 10 μg Iron (II+III) added to samples of Iron-Drugs after dissolution with 0.1 MHCl. The error did not exceed 5% with Coefficient of Variation between 2.5 - 3.3% Paired Comparison by t-test between two calibration curves showed no significant difference at 95% confidence limit.